Video over IP : - Simpson,Wes (Focal Press, 2006)
Video Over IP gives you everything you need to know to choose from among the many ways of transferring your video over a network. The information is presented in an easy to read format, with comparison charts provided to help you understand the benefits and drawbacks of different technologies for a variety of practical applications.